A comparison of patient-reported outcomes between Alloderm and Dermacell in immediate alloplastic breast reconstruction: A randomized control trial. Issue 1 (January 2021) - Stein, Michael J.; Arnaout, Angel; Lichtenstein, Julia B.; Frank, Simon G.; Cordeiro, Erin; Roberts, Amanda; Ghaedi, Bahareh; Zhang, Jing
Summary: Background: Alloderm and Dermacell are the two leading human acellular dermal matrices (ADM) in immediate breast reconstruction (IBR). Despite differences in sterility, consistency, thickness and cost, there are no comparative trials to date to compare patient-reported outcome measures (PROM) between the two products. The purpose of this study was to determine if there was a difference in patient-reported outcomes (as measured by the BREAST-Q) between patients reconstructed with Alloderm and Dermacell. Methods: A single center, open-label, randomized control trial of patients undergoing IBR with an implant for breast cancer or breast cancer prophylaxis was performed. Patients were randomized to either Alloderm or Dermacell. Baseline demographic data were compared, and linear mixed models were used to identify associations with BREAST-Q over time. Results: Between June 2016 and October 2018, 62 patients were randomized into two groups, 31(50%) Alloderm and 31(50%) Dermacell. Of these, 23(74%) patients in the Alloderm group and 27(87%) patients of the Dermacell group filled out BREAST-Q questionnaires. Baseline BREAST-Q scores with respect to satisfaction with breasts, psychosocial well-being, sexual well-being, and physical well-being were similar between groups ( p >0.05). At 3 months postoperatively, the Alloderm group had a statistically significant improvement with respect to satisfaction with breasts (67 vs 53, p  = 0.03), satisfaction with overall results (85 vs 61, p  = 0.003), satisfaction with the surgeon (89 vs 67, p  = 0.01), and satisfaction with information provided (74 vs 59, p  = 0.02). At 12 months postoperatively, there were no statistically significant differences in PROM between groups ( p >0.05). Conclusion: We report the first randomized controlled trial to date comparing patient-reported outcomes of the two most commonly used ADMs in IBR in Canada. Although a short-term analysis favors the use of Alloderm, there does not appear to be any difference in outcomes between the two products in the longer term.